Integrating the KWL Strategy with Wordwall Gamification to Enhance Reading Comprehension in Junior High School - Shafira Asti Agmal; Putri Agya Syahada; Nurwardani Abdul Wahid; Ade Restu Hermanto; Churotul Aini; Dzul Rachman (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Reading is a foundational skill in secondary English language education, essential for academic achievement and preparing learners for global contexts. Explicit instruction in reading strategies is particularly beneficial for students with limited academic English exposure. This study examines the integration of the KWL (Know, Want to know, Learned) strategy with the digital platform Wordwall, an approach designed to improve reading comprehension for junior high school students. The KWL framework enhances comprehension, focus, and engagement by activating prior knowledge, setting clear reading purposes, and encouraging reflective learning. A mixed-methods research design was employed to evaluate this intervention. The combination of structured metacognitive guidance and interactive digital activities transformed classroom instruction. Results indicated significant improvements in reading comprehension and vocabulary acquisition. Furthermore, the approach increased student motivation and established a low-anxiety environment that encouraged participation and risk-taking. The experimental group achieved a substantially higher and more consistent mean learning gain (31.05%) compared to the control group (10.73%). Their results also exhibited greater statistical stability and a distribution closer to normality, indicating that the benefits were both reliable and equitable across participants. These findings confirm that strategically combining evidence-based reading strategies with digital tools fosters a more engaging, effective, and inclusive learning environment. This pedagogical integration ultimately leads to deepened comprehension and strengthened academic outcomes, highlighting its significant potential for contemporary English language education